Realization of New Electronically Controllable Grounded and Floating Simulated Inductance Circuits Using Voltage Differencing Differential Input Buffered Amplifiers - Dinesh Prasad; D. R. Bhaskar; K. L. Pushkar (Active and Passive Electronic Components)
A new active circuit is proposed for the realisation of lossless grounded and floating inductance employing Voltage Differencing Differential Input Buffered Amplifiers (VD-DIBAs). The proposed grounded simulated inductance circuit employs two VD-DIBAs and a single-grounded capacitor whereas the floating simulated inductance circuit employs three VD-DIBAs and a grounded capacitor. The circuit for grounded inductance does not require any realization conditions whereas in case of floating inductance, only equality of two transconductances is needed. Some sample results demonstrating the applications of the new simulated inductors using VD-DIBAs have been given to confirm the workability of the new circuits.